A Comparative Study of Japanese Refusal Expressions Used by Indonesian and Native Japanese Female University Students - Afiah, Firda Nurul; Hayati, Novia; Haristiani, Nuria (Chi e Journal of Japanese Learning and Teaching, 2025)
Refusal is an essential aspect of communication that can lead to discomfort for both the refuser and the recipient. Speakers employ various refusal strategies to mitigate potential conflict and maintain social harmony. This study examines the refusal expressions used by Indonesian female university students studying Japanese and native Japanese female university students. It aims to explore how these two groups use refusal strategies in different academic settings: irai (requests), sasoi (invitations), and teian (suggestions), when interacting with both close and less close friends. Data were collected from 60 respondents using an Oral Discourse Completion Test (DCT) and analyzed based on Beebe et al.’s (1990) refusal semantic formula. The findings reveal that both groups predominantly use indirect strategies over direct ones across all scenarios. They also employ four main semantic categories in their refusals: fuka (denial), shazai (apology), riyuu (reason), and tamerai (hesitation), with riyuu and tamerai being the most frequently used. However, a notable difference emerged when refusing close friends: Indonesian Japanese learners exhibited a stronger tendency to preface refusals with shazai, suggesting a possible influence from their native language and cultural norms. These findings contribute to a deeper understanding of intercultural pragmatics and the influence of linguistic background on refusal strategies. Future research may explore refusal expressions in broader social contexts to investigate cultural and linguistic influences on politeness strategies.